Debit Air pada Saluran Sekunder Bendung Tanah Priuk Akibat Kolam Ikan Air Deras di Kabupaten Musi Rawas - Okma Yendri; Erna Purnama Sari; Rizaldi - (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2020)
The Kelingi Tugumulyo Irrigation Area is a permanent weir irrigation that runs through the building for the Satan Muara Beliti Water channel. Secondary Air Satan Muara Beliti channel has 5 buildings with the main function to flow the water through the rice fields in the Mara Beliti sub-district. Problems that arise in the distribution of water are the loss of irrigation water due to the pool of swift water and infiltration of water into the soil if the soil is saturated. These problems cause a lack of discharge for the fulfillment of irrigation water due to water loss in the secondary channel. The method used in assessing the Evaluation of Irrigation Water Provision from the Watervang Dam for Satan Water Secondary Channels was by analyzing the data of maximum discharge, minimum discharge, and average discharge of the Watervang Dam as well as calculating water demand and water availability in the Satan Muara Beliti Water Irrigation Area. There are three results about Tanah Priuk 1 weir channel (BTP1) condition. First, based on the plan discharge, according to the Kelugi Tugumulyo Irrigation network scheme, debit from BTP 1 to BTP 2 was 30.10 l/s, whereas the result from field calculation through the use of current meter was 7.89 l/sec; it means the lack of water from the plan for BTP 1 - BTP 2 which is 22.21 l/sec. Second, the debit from BTP 2 to BTP 3 was 10.80 l/sec, whereas the result from field calculation through the use of current meter was 6.20 l/s; it means the lack of water from the plan for BTP 2 - BTP 3 was 4.60 l/sec. Third, the debit from BTP 4 to BTP 5 was 11.10 l/sec, whereas the result from field calculation through the use of current meter was 6.92 l/s; it means the lack of water from the plan for BTP 4 - BTP 5 was 4.18 l/sec . It concluded that the secondary channel from BTP 5 to the village of Bali has insufficient water.